The Implementation of Inheritance Law in Muslim Communities in the City of Makassar - Andi Herawati; H. A. Qadir Gassing; H. Lomba Sultan; Abd Halim Talli (Lembaga Sembilan Tiga Community, 2019)
Rules regarding the transfer of property of a deceased person (heir) to his surviving heirs are sub-systems of Islamic inheritance law. Islam as universal teaching teachers and regulates all aspects of human life with the aim that humans get the benefit of life both in the world and in the hereafter. Therefore Allah's rules can be understood and practiced based on their intellectual aspects and can also be understood and practiced based on their contextual aspects, in order to create a human society in general and family in particular. So that is why the Muslim community of the city of Makassar is more inclined to carry out the distribution of inheritance based on an agreement by way of deliberation. Such resolution efforts are called resolutions through non-litigation channels, while efforts to distribute inheritance through court decisions are called settlement through litigation.